Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T20:11:58+01:00
A)
-7x^2 + 42x = 0
-7x(x-6) = 0
-7x = 0 lub x-6 = 0
x = 0 lub x=6

b)
9x^2 + 1/3x = 0
x(9x + 1/3) = 0
x = 0 lub 9x + 1/3 = 0
x = 0 lub 9x = -1/3
x = 0 lub x = -3

c)
36x^2 = 6x
36x^2 - 6x = 0
6x(6x-1) = 0
6x = 0 lub 6x-1 = 0
x = 0 lub 6x = 1
x = 0 lub x = 1/6

d)
2x + 18x^2 = 0
2x(1+9x) = 0
2x = 0 lub 1+9x = 0
x = 0 lub 9x = -1
x = 0 lub x = -1/9
3 4 3
2010-03-16T20:14:37+01:00
A)-7x^2 + 42x = 0
x(-7x+42)=0
x=0 lub -7x+42=0
-7x=-42
x= 6
b)9x^2 + 1/3x = 0
x(9x+1/3)=
x=0 lub 9x+1/3=0
9x=-1/3
x= -1/27
c)36x^2 = 6x
36x^2-6x=0
x(36x-6)=0
x=0 lub 36x-9=0
36x=9
x= 0,25
d)2x + 18x^2 = 0
x(2+18x)=0
x=0 lub 2+18x=0
18x=2
x= 0,11
2 5 2